THE DIFFERENCES IN THE INTERPRETATION OF RAVNAK’S WORKS IN LITERATURE - Usmonova Mohidil (Journals Park Publishing, 2024)
The article is provuded to the interpretation of Pahlavi Ravnak’s lyrical heritage in scientific literature. Controversial aspects of the interpretations given in scientific sources are explored.
Keywords: poem, rhyme, radif, literary analysis, interpretation